Andean Lupin (Lupinus mutabilis Sweet) a plant with nutraceutical and medicinal potential - Chirinos-Arias, M.C. (Revista Bio Ciencias, 2015)
Comments on the report regarding the case “First record of the neotropical otter Lontra longicaudis annectens (Carnivora, Mustelidae) in the estuary Boca Negra, Jalisco, Mexico: an approach to understanding its diet” from Rodriguez- Uribe, Rubio-Padilla and Navarro-Rodriguez (2015).